A STUDY ON THE ANTIOXIDANT EFFECT OF CORIOLUS VERSICOLOR POLYSACCHARIDE IN RAT BRAIN TISSUES - Chen, Jiayu; Jin, Xiaoyan; Zhang, Liting; Yang, Linjun (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
The objective of the study was to investigate the antioxidant effect of Chinese medicine Coriolus versicolor polysaccharide on brain tissue and its mechanism in rats. SOD, MDA and GSH-Px levels in rat brain tissues were determined with SD rats as the animal model. The results showed that Coriolus versicolor polysaccharide can reduce the lipid peroxidation level in brain tissues during exhaustive exercise in rats, and can accelerate the removal of free radicals. The study concluded that its antioxidant effect is relatively apparent.